Deep Rolling Techniques: A Comprehensive Review of Process Parameters and Impacts on the Material Properties of Commercial Steels - Dilifa Jossley Noronha; Sathyashankara Sharma; Raghavendra Prabhu Parkala; Gowri Shankar; Nitesh Kumar; Srinivas Doddapaneni (Metals, 2024)
The proposed review demonstrates the effect of the surface modification process, specifically, deep rolling, on the material surface/near-surface properties of commercial steels. The present research examines the various process parameters involved in deep rolling and their effects on the material properties of AISI 1040 steel. Key parameters such as the rolling force, feed rate, number of passes, and roller geometry are analyzed in detail, considering their influence on residual stress distribution, surface hardness, and microstructural alterations. Additionally, the impact of deep rolling on the fatigue life, wear resistance, and corrosion behavior of AISI 1040 steel is discussed. Engineering components manufactured by AISI 1040 steel can perform better and last longer when deep rolling treatments are optimized with an understanding of how process variables and material responses interact. This review provides critical insights for researchers and practitioners interested in harnessing deep rolling techniques to enhance the mechanical strength and durability of steel components across diverse industrial settings. In summary, the valuable insights provided by this review pave the way for continued advancements in deep rolling techniques, ultimately contributing to the development of more durable, reliable, and high-performance steel components in diverse industrial applications. The establishment of generalized standardizations for the deep rolling process proves unfeasible because of the multitude of controlling parameters and their intricate interactions. Thus, specific optimization studies tailored to the material of interest are imperative for process standardization. The published literature on the characterization of surface and subsurface properties of deep-rolled AISI 1040 steel, as well as process parameter optimization, remains limited. Additionally, numerical, analytical, and statistical studies and the role of ANN are limited compared with experimental work on the deep rolling process.